A study on two variable analogues of certain fractional integral operators - Ahmad Khan, Mumtaz; Salama Abukhammash, Ghazi (Pro Mathematica, 2003)
The Paper deals with a two variable analogues of certain fractional integral operators introduced by M. Saigo. Besides giving two variable analogues of earlier known fractional integral operators of one variable as special cases of newly defined operators, the paper establishes certain results in the form of theorems including integration by parts.